Comparison of chlorination and chloramination practices on microbial inactivation efficiencies within a scaled‐up water distribution network using central composite design. (17th August 2020) - Khan, Romana; Hashmi, Imran; Qureshi, Amrah; Rasheed, Sajida
Abstract: Disinfection practices reduce the incidence of water‐borne diseases but may result in formation of disinfection byproducts (DBPs) in raw water that are reported to be carcinogenic. Central composite design (CCD) was employed in the present study for optimization of disinfectant dose and contact time with the rationale to evaluate if an optimal balance could be achieved between minimal DBPs formation and effective microbial inactivation with either free or combined chlorine in treated water within a lab‐scale prototype network to simulate real water distribution network conditions. After a series of experimental runs based upon design of experiments (DoE) by CCD, dose was found to be the most significant factor ( P  < 0.01) in determining DBPs formation in both disinfectant's applications. Where, contact time significantly ( P  < 0.01) affected bacterial inactivation in chlorination experiments, in contrast, dose was effective in chloramination experiments. Thus, it was concluded that the optimal balance may be achieved in the water networks with the help of multifactorial optimization when disinfectant dose was maintained near 3 mg/L as applied chlorine dose in both disinfection cases, while contact time was 62 and 155 min for chlorine and chloramine, respectively. Abstract :